2021
DOI: 10.1080/07391102.2021.1921033
|View full text |Cite
|
Sign up to set email alerts
|

Antivirals virtual screening to SARS-CoV-2 non-structural proteins

Abstract: In March 2020, the World Health Organization (WHO) declared coronavirus disease-19 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a pandemic. Since then, the search for a vaccine or drug for COVID-19 treatment has started worldwide. In this regard, a fast approach is the repurposing of drugs, primarily antiviral drugs. Herein, we performed a virtual screening using 22 antiviral drugs retrieved from the DrugBank repository, azithromycin (antibiotic), ivermectin (antinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Many studies have demonstrated that targeting the virus-specific proteins is an effective strategy for drug discovery towards developing direct-acting antivirals [16][17][18]. Based on complementary approaches using both in vitro experiments and in silico virtual screenings, many drug discoveries are initiated by exploiting the effect of natural substances, including flavonoids, on essential coronavirus enzymes as a drug target (Figure 2) [19][20][21][22][23]. While in silico approaches such as molecular dynamics and structure-based virtual screening represent some of the early steps of drug discovery, in vitro studies utilize the findings to narrow down further and experiment with the most promising compounds in cell-based or cell-free methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that targeting the virus-specific proteins is an effective strategy for drug discovery towards developing direct-acting antivirals [16][17][18]. Based on complementary approaches using both in vitro experiments and in silico virtual screenings, many drug discoveries are initiated by exploiting the effect of natural substances, including flavonoids, on essential coronavirus enzymes as a drug target (Figure 2) [19][20][21][22][23]. While in silico approaches such as molecular dynamics and structure-based virtual screening represent some of the early steps of drug discovery, in vitro studies utilize the findings to narrow down further and experiment with the most promising compounds in cell-based or cell-free methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers adopted MM/PB(GB)SA calculations to screen drugs or compounds against multiple targets of SARS-CoV-2. Nunes et al 555 docked 24 approved drugs to SARS-CoV-2 Mpro, PLpro, and the ADP ribose phosphatases of nsp3, nsp9, nsp12, nsp15, and nsp16. The MM/GBSA calculations were further performed on the top three drugs from docking tests.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…Recently, immunocompromised COVID-19 patients have been suffering from the coinfection of black fungus (mucormycosis) [ 8 , 9 ]. COVID-19 patients with a compromised immune system or having diabetic ketoacidosis are highly prone to mucormycosis [ 10 13 ]. Rhizomucor, a black fungus species, causes more than 75% of cases of mucormycosis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%